El status qualitatis de la relatio en el texto epigráfico del senado consulto de Gneo Pisón Padre - Ruiz Castellanos, Antonio; Lomas Salmonte, Francisco Javier (Gerión. Revista de Historia Antigua, 2002)
We intend in this paper to solve the difficulty that it presents the expression of the relatio of the Senatus Consultus (SC) of Gnaeus Piso: ad senatum retulit quails causa Cn. Pisonis patris visa esset[...] et qualis causa M.Pisonis visa esset[...] qualis causa Planiciae visa esset ... With this expression, we believe, the SC refers to the juridical and rhetorical position the causes of the Pison’s had. This meaning is confirmed when we contrast the epigraphic SC with Annales 3. 12-18 of Tacit. The consequences that are derived of this interpretation of the formula of the epigraphic SC, are: 1. About the political objectives that Tiberius pursued with this of outlining the relatio in the SC; and 2. About the historicity of this document.